TaWAK2A-800, a Wall-Associated Kinase, Participates Positively in Resistance to Fusarium Head Blight and Sharp Eyespot in Wheat - Feilong Guo (MDPI AG, 2021)
Fusarium head blight (FHB) and sharp eyespot are important diseases of the cereal plants, including bread wheat (Triticum aestivum) and barley. Both diseases are predominately caused by the pathogenic fungi, Fusarium graminearum and Rhizoctonia cerealis. The roles of the wheat-wall-associated kinases (WAKs) in defense against both F. graminearum and R. cerealis have remained largely unknown. This research reports the identification of TaWAK2A-800, a wheat WAK-coding gene located on chromosome 2A, and its functional roles in wheat resistance responses to FHB and sharp eyespot. TaWAK2A-800 transcript abundance was elevated by the early infection of R. cerealis and F. graminearum, or treatment with exogenous chitin. The gene transcript seemed to correspond to the resistance of wheat. Further functional analyses showed that silencing TaWAK2A-800 compromised the resistance of wheat to both FHB (F. graminearum) and sharp eyespot (R. cerealis). Moreover, the silencing reduced the expression levels of six defense-related genes, including the chitin-triggering immune pathway-marker genes, TaCERK1, TaRLCK1B, and TaMPK3. Summarily, TaWAK2A-800 participates positively in the resistance responses to both F. graminearum and R. cerealis, possibly through a chitin-induced pathway in wheat. TaWAK2A-800 will be useful for breeding wheat varieties with resistance to both FHB and sharp eyespot.